2022
DOI: 10.1038/s42255-022-00707-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of hexokinase 2 in shaping microglial function by gating glycolytic flux and mitochondrial activity

Abstract: Microglia continuously survey the brain parenchyma and actively shift status following stimulation. These processes demand a unique bioenergetic programme; however, little is known about the metabolic determinants in microglia. By mining large datasets and generating transgenic tools, here we show that hexokinase 2 (HK2), the most active isozyme associated with mitochondrial membrane, is selectively expressed in microglia in the brain. Genetic ablation of HK2 reduced microglial glycolytic flux and energy produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 69 publications
(111 reference statements)
0
44
0
Order By: Relevance
“…The role of HK2 in inflammation regulation remains elusive. While some studies reported that inhibition of HK2 attenuates inflammation and alleviates pathogenesis of colitis and pulmonary arterial hypertension by inhibiting glycolysis (Hinrichsen et al, 2021; Liu et al, 2020), we found that Hk2 deletion in microglia potentiates inflammation and injury in a mouse model of ischemic stroke by impairing mitochondrial functions (Y. Hu et al, 2022). Here we show that Hk2 deletion in myeloid cells reduced inflammation in DRG and elicited analgesic effects.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The role of HK2 in inflammation regulation remains elusive. While some studies reported that inhibition of HK2 attenuates inflammation and alleviates pathogenesis of colitis and pulmonary arterial hypertension by inhibiting glycolysis (Hinrichsen et al, 2021; Liu et al, 2020), we found that Hk2 deletion in microglia potentiates inflammation and injury in a mouse model of ischemic stroke by impairing mitochondrial functions (Y. Hu et al, 2022). Here we show that Hk2 deletion in myeloid cells reduced inflammation in DRG and elicited analgesic effects.…”
Section: Discussionmentioning
confidence: 53%
“…To investigate whether HK2 levels are changed after SNI, we used a HK2‐reporter line, in which a P2A CreER ‐P2A‐tdTomato (tdT) cassette was inserted before the stop codon of HK2 (Figure 1a). The tdT fluorescence in this transgenic mouse line recapitulates the expression levels of HK2 in vivo (Hu et al, 2022), allowing us to temporally track the expression of HK2 after nerve injury. Since the increase in SDH microglia reaches a peak 7 days after nerve injury, we mainly focused our observation during the first week in SNI models (Kobiela Ketz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations